MANAJEMEN STOK PERUSAHAAN EKSPEDISI J&T EXPRESS JOMBANG PERSPEKTIF ETIKA BISNIS SYARI’AH: Stock Management of J&T Express Jombang Expedition Company - yeni anggraeni; Azizah, Ninik (Irtifaq, 2026)
The development of globalization and advances in information technology have increased trade activities, especially through e-commerce, thus driving the increasing need for goods delivery services. Expedition companies play an important role in ensuring that goods arrive at their destinations on time, safely, and according to customer expectations. One important aspect in the operations of expedition companies is package stock management which includes the process of recording, storing, sorting, and distributing packages. This study aims to analyze package stock management at J&T Express Jombang from the perspective of sharia business ethics, specifically based on the principles of trust, honesty (sidq), justice ('adl), and responsibility. This study uses a qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The research method used is an empirical juridical method with a conceptual approach. Data were obtained through interviews, observations, and document analysis related to Stock Management of J&T Express Jombang Expedition Company from the Perspective of Sharia Business Ethics. This study identifies Stock Management of J&T Express Jombang Expedition Company from the Perspective of Sharia Business Ethics. Furthermore, the data was analyzed based on the principles of Sharia Business Ethics. The results of the study on package stock management at J&T Express Jombang were systematically implemented using the digital J&T Marking System (JMS) and coordination between operational departments. This system supports the implementation of Sharia business ethics principles, namely siddiq (honesty) through package data verification, amanah (responsibility) in package safeguarding, fathanah (professionalism) through the use of digital systems, tabligh (transparency) through communication and package tracking, and istiqamah (consistency) through routine checks according to procedures. The study concluded that package stock management has been running well, but improvements in accuracy, supervision, and coordination are still needed to minimize errors and ensure optimal implementation of Sharia business ethics principles for more effective and reliable service. Professionalism (fathanah), communication (tabligh), and consistency (istiqamah) can be optimally implemented to improve service quality and effectiveness.